Question
I don't understand how when integrating over the parameters in the posterior predictive, the integration "disappears". It's hard for me to ask simply because I am confused, so here is an example.
Example
Imagine we have a Gaussian model with unknown mean $\mu$ and fixed variance $\sigma^2$. If $D$ is the training data and $D'$ is unseen data, then the posterior predictive is
$$ \begin{align} p(D' \mid D) &= \int p(D' \mid D, \mu) p(\mu \mid D) d\mu \\ &\stackrel{\star}{=} \int p(D' \mid \mu) p(\mu \mid D) d\mu \\ &\triangleq \int \mathcal{N}(D' \mid \mu, \sigma^2) \mathcal{N}(\mu \mid \mu_N, \sigma_N^2) d \mu \end{align} $$
where step $\star$ holds because the modeling assumption is that $D'$ is conditionally independent from $D$ given $\mu$ and the definitions of $\mu_N$ and $\sigma_N^2$ fall out of computing the posterior. See Bishop (2006) page 98 for details.
Here is where I am confused. I can show that
$$ \mathcal{N}(D' \mid \mu, \sigma^2) \mathcal{N}(\mu \mid \mu_N, \sigma_N^2) = \mathcal{N}(D' \mid \mu_N, \sigma_N^2 + \sigma^2) $$
Murphy's derivation in Conjugate Bayesian analysis of the Gaussian distribution suggests looking at Bishop, equation 2.115 (see my edit for more). My trouble is, Murphy then claims that
$$ p(D \mid D') = \mathcal{N}(D' \mid \mu_N, \sigma_N^2 + \sigma^2) $$
which is what I mean by the integration should "disappearing". What happened? I understand that this new distribution has no dependence on $\mu$, but I would have expected
$$ \begin{align} p(D' \mid D) &= \int \mathcal{N}(D' \mid \mu, \sigma^2) \mathcal{N}(\mu \mid \mu_N, \sigma_N^2) d \mu \\ &= \int \mathcal{N}(D' \mid \mu_N, \sigma_N^2 + \sigma^2) d \mu \\ &= \mathcal{N}(D' \mid \mu_N, \sigma_N^2 + \sigma^2) \int d \mu \end{align} $$
But it's unclear what becomes of the integral. It's not a probability, so it's not like this is guaranteed to be 1.
Edit
This is my derivation based on Murphy's hint to look at Bishop (2006), page 93. Since both our posterior and prior are Gaussians, we can use the following fact:
$$ \begin{align} p(\textbf{x}) &= \mathcal{N}(\textbf{x} \mid \boldsymbol{\mu}, \boldsymbol{\Psi}) \\ p(\textbf{y} \mid \textbf{x}) &= \mathcal{N}(\textbf{y} \mid A \textbf{x} + \textbf{b}, \textbf{P}) \\ &\Downarrow \\ p(\textbf{y}) &= \mathcal{N}(\textbf{y} \mid \textbf{A} \boldsymbol{\mu} + \textbf{b}, \textbf{P} + \textbf{A} \boldsymbol{\Psi} \textbf{A}^{\top}) \end{align} $$
where we have
$$ \begin{align} \textbf{x} &= \mu \\ \boldsymbol{\mu} &= \mu_N \\ \boldsymbol{\Psi} &= \sigma_N^2 \\ \textbf{y} &= D' \\ \textbf{A} &= 1 \\ \textbf{b} &= 0 \\ \textbf{P} &= \sigma^2 \end{align} $$
This gives us
$$ \begin{align} p(\mu) &= \mathcal{N}(\mu \mid \mu_N, \mu_N^2) \\ p(D' \mid \mu) &= \mathcal{N}(D' \mid \mu, \sigma^2) \\ p(D' \mid \mu) p(\mu) = p(D') &= \mathcal{N}(D' \mid \mu_N, \sigma^2 + \sigma_N^2) \end{align} $$
We can add conditioning on $D$ at every step if we'd like, since it doesn't effect the distributions provided we have the parameters (i.i.d.):
$$ \begin{align} p(\mu \mid D) &= \mathcal{N}(\mu \mid \mu_N, \mu_N^2) \\ p(D' \mid \mu, D) &= \mathcal{N}(D' \mid \mu, \sigma^2) \\ p(D' \mid \mu, D) p(\mu) = p(D' \mid D) &= \mathcal{N}(D' \mid \mu_N, \sigma^2 + \sigma_N^2) \end{align} $$